More kinds of being : a further study of individuation, identity, and the logic of sortal terms - Lowe, E. J. (E. Jonathan) (Wiley-Blackwell, 2009)
Taking into account significant developments in the metaphysical thinking of E.J. Lowe over the past 20 years, More Kinds of Being:A Further Study of Individuation, Identity, and the Logic of Sortal Terms presents a thorough reworking and expansion of the 1989 edition of Kinds of Being.: Brings many of the original ideas and arguments put forth in Kinds of Being thoroughly up to date in light of new developments; Features a thorough reworking and expansion of the earlier work, rather than just a new edition; Reflects the author's conversion to what he calls 'the four-category ontology, ' a met.